Innovations and income inequalities – a comparative study - Julia Włodarczyk (Journal of International Studies)
Due to the complexity of relationships between innovations and income inequalities, the choice of measures to be taken in the course of their interaction is very important. This paper presents a regression analysis based on the selected measures of innovativeness (gross domestic expenditure on R&D, number of patent applications, the Creative Economy Index), income inequalities (Gini coefficient, top 3% and top 1% shares of national equalized income) and various control variables retrieved mostly from the Eurostat Database for 30 countries (European Union countries, Iceland, Norway) for the study period of 2005-2014. It has been found that higher gross domestic expenditure on R&D as a percentage of GDP tends to increase inequalities, while higher number of patent applications and higher value of the Creative Economy Index have the opposite effect. Besides, top income inequality is partly driven by different factors than broader measures of income inequalities.